OTUD5 Variants Associated With X-Linked Intellectual Disability and Congenital Malformation - Saida, Ken; Fukuda, Tokiko; Scott, Daryl A.; Sengoku, Toru; Ogata, Kazuhiro; Nicosia, Annarita; Hernandez-Garcia, Andres; Lalani, Seema R.; Azamian, Mahshid S.; Streff, Haley; Liu, Pengfei; Dai, Hongzheng; et al. (Frontiers in Cell and Developmental Biology, 2021)
Background X-linked intellectual disability (XLID), which occurs predominantly in males, is a relatively common and genetically heterogeneous disorder in which over 100 mutated genes have been reported. The OTUD5 gene at Xp11.23 encodes ovarian tumor deubiquitinase 5 protein, which is a deubiquitinating enzyme member of the ovarian tumor family. LINKage-specific-deubiquitylation-deficiency-induced embryonic defects (LINKED) syndrome, arising from pathogenic OTUD5 variants, was recently reported as a new XLID with additional congenital anomalies. Methods We investigated three affected males (49- and 47-year-old brothers [Individuals 1 and 2] and a 2-year-old boy [Individual 3]) from two families who showed developmental delay. Their common clinical features included developmental delay, hypotonia, short stature, and distinctive facial features, such as telecanthus and a depressed nasal bridge. Individuals 1 and 2 showed epilepsy and brain magnetic resonance imaging showed a thin corpus callosum and mild ventriculomegaly. Individual 3 showed congenital malformations, including tetralogy of Fallot, hypospadias, and bilateral cryptorchidism. To identify the genetic cause of these features, we performed whole-exome sequencing. Results A hemizygous OTUD5 missense variant, c.878A>T, p.Asn293Ile [NM_017602.4], was identified in one family with Individuals 1 and 2, and another missense variant, c.1210 C>T, p.Arg404Trp, in the other family with Individual 3, respectively. The former variant has not been registered in public databases and was predicted to be pathogenic by multiple in silico prediction tools. The latter variant p.Arg404Trp was previously reported as a pathogenic OTUD5 variant, and Individual 3 showed a typical LINKED syndrome phenotype. However, Individuals 1 and 2, with the novel variant (p.Asn293Ile), showed no cardiac or genitourinary malformations. Conclusions Unlike previous reports of LINKED syndrome, which described early lethality with congenital cardiac anomalies, our three cases are still alive. Notably, the adult brothers with the novel missense OTUD5 variant have lived into their forties. This may be indicative of a milder phenotype as a possible genotype-phenotype correlation. These findings imply a possible long-term prognosis for individuals with this new XLID syndrome, and a wider phenotypic variation than initially thought.